2009
DOI: 10.1348/014466608x288827
|View full text |Cite
|
Sign up to set email alerts
|

When does national identification lead to the rejection of immigrants? Cross‐sectional and longitudinal evidence for the role of essentialist in‐group definitions

Abstract: Two studies were carried out in England to investigate the role of essentialist national group definitions in determining the effect of national identification on prejudice towards immigrants, and asylum seekers in particular. It was expected that the relationship between national identification and prejudice would depend on the degree to which participants endorse an essentialist ('ethnic') definition of their nationality. Consistent with this, Study 1 (N=154) found that national identification is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
181
3
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(196 citation statements)
references
References 27 publications
(29 reference statements)
4
181
3
8
Order By: Relevance
“…Thus it is not identification per se that drives anti-immigration stances, but rather the meaning that individuals and groups attribute to identity (Reicher & Hopkins, 2001). Research has for example shown that national identification was related to prejudice towards asylum seekers in England only to the extent that people endorsed an ethnic conception of the nation, that is based on ancestry and blood ties (Pehrson, Brown, & Zagefka, 2009; see also Meeus, Duriez, Vanbeselaere, & Boen, 2010). In a study highlighting the importance of representations of national history, the experimentally emphasized Christian roots of Dutch nationhood led low national identifiers to oppose rights of Muslim immigrants to the same extent as did high identifiers (Smeekes, Verkuyten, & Poppe, 2011).…”
Section: National Identification and Threatmentioning
confidence: 99%
“…Thus it is not identification per se that drives anti-immigration stances, but rather the meaning that individuals and groups attribute to identity (Reicher & Hopkins, 2001). Research has for example shown that national identification was related to prejudice towards asylum seekers in England only to the extent that people endorsed an ethnic conception of the nation, that is based on ancestry and blood ties (Pehrson, Brown, & Zagefka, 2009; see also Meeus, Duriez, Vanbeselaere, & Boen, 2010). In a study highlighting the importance of representations of national history, the experimentally emphasized Christian roots of Dutch nationhood led low national identifiers to oppose rights of Muslim immigrants to the same extent as did high identifiers (Smeekes, Verkuyten, & Poppe, 2011).…”
Section: National Identification and Threatmentioning
confidence: 99%
“…Prejudice was operationalized as negative affect elicited by members of the target immigrant group. Negative affect is a fundamental component of prejudice and the use of affective measures of prejudice has ample precedent in the literature [32].…”
Section: The Mechanism Of Anti-corporate Prejudice In a Crisismentioning
confidence: 99%
“…Based on existing researches [30][31][32], the concept of anti-corporate prejudice was defined the negative bias formed by negative feelings about a corporate crisis and the information withdrawn from memory (e.g., negative business information, scandals, rumors, etc.). Furthermore, to better measure the biased attitudes to the corporate crisis, this study employed the concept of prejudice with negative emotion and stereotypes.…”
Section: The Mechanism Of Anti-corporate Prejudice In a Crisismentioning
confidence: 99%
“…Although people in Scotland are often described as having relatively positive views of immigration (Rolfe & Metcalf, 2009), their enthusiasm has recently been questioned. Bond (2006) reported that Scots were reluctant to see visible minorities as Scottish, and Pehrson, Brown, & Zagefka (2009) found that those who held an ethnic rather than civil conception of nationalism were relatively opposed to immigration. Most recently, McCollum, Nowok, and Tindal (2014) showed that disadvantaged groups in Scotland, such as those with few qualifications, “are comparatively unreceptive to migrants and overall levels of opposition to migration may be increasing” (p. 99).…”
Section: Regeneration and Diversity In Glasgowmentioning
confidence: 99%